POTENSI METABOLIT SEKUNDER ANTIFUNGI AKTINOMISETES YANG DIISOLASI DARI TANAH MANGROVE WONOREJO SURABAYA TERHADAP Trichophyton rubrum - Febrianti Fitria; Sasongkowati Retno; Anggraini Anita Dwi (Analis Kesehatan Sains, 2021)
Actinomycetes are gram-positive bacteria that have aerobic properties. Actinomycetes have the ability to produce antibiotic compounds. Actinomycetes are the second largest organisms that live in soil with a population of 1-10 million per gram of soil. Actinomycetes also make up 10-50% of the microbes in the soil. The purpose of this study was to determine the antifungal activity of actinomycetes isolates isolated from the soil of the Mangrove Wonorejo forest in Surabaya against the fungus Trichophyton rubrum. This type of research is an experimental laboratory with quantitative analysis. Actinomycetes isolates were taken from 3 different soil locations, pretreatment by heat treatment at 90°C for 15 minutes. Actinomycetes were isolated on casein starch agar medium which had been added with 0.002% Nystatin. Selection of antimicrobial compounds was based on the disc diffusion method which was characterized by the formation of a zone of inhibition around the disc. The results showed that from 3 locations of soil sampling, 8 actinomycetes isolates were obtained, but only 6 isolates were able to inhibit the fungus Trichophyton rubrum. showed that isolates C3-2, B3-1, C4-1, were categorized as having very strong inhibitory power. While isolates A5-1, A3-2 were categorized as having inhibitory power and isolates A4-1 and A4-2 were categorized as having moderate inhibitory power against the fungus Trichophyton rubrum.